2012
DOI: 10.15517/rbt.v60i4.2184
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns of stream-dwelling fishes from Mata Atlântica, Southeast Brazil

Abstract: Abstract:The identification of mechanisms of spatial-temporal variation, obtained from the quantification of natural populations, is a central topic of ecological research. Despite its importance to life-history theory, as well as to conservation and management of natural populations, no studies concerning movement patterns and home range of small stream-dwelling fishes from Brazilian rain forests are known. In the present study we aimed to describe the longitudinal pattern of long distance movement as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 46 publications
(38 reference statements)
0
8
0
7
Order By: Relevance
“…We found that 19 out of the 34 species captured in the present study (aproximately 55%) are present both in streams and the main rivers of the basin (Ferreira & Petrere Jr., 2009). In addition, Mazzoni et al (2004) and Mazzoni & Iglesias-Rios (2007) found evidence of short reproductive migrations for some species of Characidae of Atlantic forest streams, while Mazzoni & Iglesias-Rios (2012) by means of a mark-recapture experiment, found a group of fishes (Astyanax janeiroensis, A. hastatus, Parotocinclus maculicauda, and Pimelodella lateristriga), which they called "Long Movement group", that moved at least 6 km within 60 days. Nonetheless, the Mantel test indicated a non-significant influence of site proximities upon assemblage structure, suggesting that including a third spatial matrix would be unhelpfull to reduce significantly the unexplained variation of fish-environment association.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 19 out of the 34 species captured in the present study (aproximately 55%) are present both in streams and the main rivers of the basin (Ferreira & Petrere Jr., 2009). In addition, Mazzoni et al (2004) and Mazzoni & Iglesias-Rios (2007) found evidence of short reproductive migrations for some species of Characidae of Atlantic forest streams, while Mazzoni & Iglesias-Rios (2012) by means of a mark-recapture experiment, found a group of fishes (Astyanax janeiroensis, A. hastatus, Parotocinclus maculicauda, and Pimelodella lateristriga), which they called "Long Movement group", that moved at least 6 km within 60 days. Nonetheless, the Mantel test indicated a non-significant influence of site proximities upon assemblage structure, suggesting that including a third spatial matrix would be unhelpfull to reduce significantly the unexplained variation of fish-environment association.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in tropical streams (e.g. Mazzoni, Iglesias-Rios, 2012;Mazzoni et al, 2015) revealed that fishes move longer distances than that mentioned by Gerking (1959). Mazzoni, IglesiasRios (2012) registered fish movement in a tropical stream and suggested that they were mainly motivated by reproduction.…”
Section: Original Articlementioning
confidence: 82%
“…and A. janeiroensis were recaptured just near the marking site, moving through short distances. Fishes with restricted movement and small home-ranges face different challenges when compared to those with longer distance movement (Mazzoni, Iglesias-Rios, 2012). Cichlidae (G. brasiliensis) and Loricariidae (H. punctatus and Rineloricaria sp.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations